Layered zinc hydroxide monolayers by hydrolysis of organozincs. Issue 8 (25th January 2018) - Leung, Alice H. M.; Pike, Sebastian D.; Clancy, Adam J.; Yau, Hin Chun; Lee, Won Jun; Orchard, Katherine L.; Shaffer, Milo S. P.; Williams, Charlotte K.
Abstract : Organometallic precursors provide a new and clean route to solutions of 2D materials relevant for applications including catalysis, electronics and sensing. Abstract : 2D inorganic materials and their exfoliated counterparts are both of fundamental interest and relevant for applications including catalysis, electronics and sensing. Here, a new bottom-up synthesis route is used to prepare functionalised nanoplatelets, in apolar organic solvents, via the hydrolysis of organometallic reagents; the products can be prepared in high yield, at room temperature. In particular, a series of layered zinc hydroxides, coordinated by aliphatic carboxylate ligands, were produced by the hydrolysis of diethyl zinc and zinc carboxylate mixtures, optimally at a molar ratio of [COOR]/[Zn] = 0.6. Layered zinc hydroxides coordinated by oleate ligands form high concentration solutions of isolated monolayers (3 nm thick x ∼ 26 nm) in apolar organic solvents (up to 23 mg mL −1 in toluene), as confirmed by both atomic force and transmission electron microscopies of deposited species. The high solubility of the product allows the synthetic pathway to be monitored directly in situ through 1 H NMR spectroscopy. The high solubility also provides a route to solution deposition of active functional materials, as illustrated by the formation of nanoporous films of optically transparent porous zinc oxide (1 μm thickness) after annealing at 500 °C. This new organometallic route to 2D materials obviates common complications of top-down exfoliation syntheses, including sonochemical-degradation and low yields of aggregated polydispersed layers, and may potentially be extended to a wide range of systems.